Electrical characterization of n-doped SiGeSn diodes with high Sn content - Clausen, Caterina J.; Fischer, Inga A.; Weisshaupt, David; Baerwolf, Florian; Tillack, Bernd; Colston, Gerard; Myronov, Maksym; Oehme, Michael; Schulze, Jörg (Semiconductor Science and Technology, 2018)
Diodes incorporating undoped and Sb-doped Si x Ge1-x-ySn y layers grown by molecular beam epitaxy with different alloy compositions and lattice-matched to Ge were fabricated and characterized experimentally. We discuss material as well as electrical device characterization and investigate different contact metallizations (Ni and Al). In particular, we investigate the formation of Ni(Si x Ge1-x-ySn y ) on the doped Sb-doped Si x Ge1-x-ySn y layers via annealing based on material characterization and measurements of specific contact resistivities. Our results can serve as a starting point for the investigation of Si x Ge1-x-ySn y layers with high Si and Sn content as cladding material in optoelectronic devices such as lasers and light emitting diodes.
CRIS-Team Scopus Importer:2021-06-29
Keywords: annealing; Ni; Ni(SiGeSn); Sb doping SiGeSn; SiGeSn; Sn